Gender in Distress: Compulsory Heterosexuality in Chappell Roan's Song Good Luck, Babe! - Ibrahim, Laila Nabilahtuzzahro; Calista, Salsabila Nova; Smarandreetha, Falsyawal Galang (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This article investigates how gender security matters through compulsory heterosexuality in Chappell Roan's Song Good Luck, Babe. In a world dominated by heteronormativity, heterosexuality has long been considered the standard for sexual and romantic relationships that enforces a strict gender binary. Consequently, individuals in heteronormative societies who have homosexual and queer tendencies feel inevitably obligated to pursue heterosexual relationships, even if those do not bring genuine satisfaction and shapes further gender insecurities. This phenomenon is known as Compulsory Heterosexuality as theorized by Adrienne Rich. Through qualitative method and explorative approach within gender and cultural studies, this research deconstructs the elements of compulsory heterosexuality, exploring their influence on heteronormative norms and gender expectations in a song as a type of literary work. The analysis also shows how any compulsory heterosexuality will never bind people to find freedom in other gender security. In conclusion, compulsory heterosexuality significantly shapes individual identities, often leading to confusion and gender distress for those who cannot fully express or embrace their homosexual selves